2018
DOI: 10.1038/s41467-018-04140-9
|View full text |Cite
|
Sign up to set email alerts
|

An effector from the Huanglongbing-associated pathogen targets citrus proteases

Abstract: The citrus industry is facing an unprecedented challenge from Huanglongbing (HLB). All cultivars can be affected by the HLB-associated bacterium ‘Candidatus Liberibacter asiaticus’ (CLas) and there is no known resistance. Insight into HLB pathogenesis is urgently needed in order to develop effective management strategies. Here, we use Sec-delivered effector 1 (SDE1), which is conserved in all CLas isolates, as a molecular probe to understand CLas virulence. We show that SDE1 directly interacts with citrus papa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
156
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(170 citation statements)
references
References 62 publications
3
156
0
1
Order By: Relevance
“…SDEs of Las have been explored to understand virulence, survival, and detection (Prasad et al , ; Pagliaccia et al , ; Shi et al , ). Las SDE1 targets citrus papain‐like cysteine proteases, which are induced during infection and known to be plant immune regulators (Clark et al , ). SDE1 also induces starch formation and chlorosis after transient expression in Nicotiana benthamiana (Pitino et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SDEs of Las have been explored to understand virulence, survival, and detection (Prasad et al , ; Pagliaccia et al , ; Shi et al , ). Las SDE1 targets citrus papain‐like cysteine proteases, which are induced during infection and known to be plant immune regulators (Clark et al , ). SDE1 also induces starch formation and chlorosis after transient expression in Nicotiana benthamiana (Pitino et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike most gram‐negative bacteria, Las lacks the type III secretion system, but possesses the general Sec secretion system, which is capable of secreting effectors directly outside bacterial cells (Sugio et al , ). Sec translocon‐dependent effectors (SDEs) are among the most likely Las virulence components (Pagliaccia, et al , ; Clark et al , ). However, the host targets of Las SDEs remain relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms of infected trees include leaf mottling, deformed/discolored fruits, premature fruit drop, and premature mortality [2]. It has been suggested that CLas encoded proteins have an inhibitory effect in plant defenses [3,4], but a comprehensive mechanism of infection is still lacking. No effective disease management practice is currently available.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, P. infestans secretes Kazal-like serine protease inhibitors, including the EPI1 and EPI10 proteins that inhibit tomato subtilase P69B(Tian et al, 2004; Tian et al, 2005). More recently, a study on the pathogenicity of Huanglongbing uncovered the Candidatus Liberibacter asiaticus effector SDE1 that directly interacts with and inhibits citrus PLCP activity(Clark et al, 2018). In another case, the cyst nematode Heterodera schachtii effector protein 4E02 repurposes a PLCP from its role in defense by targeting it to distinct plant cell compartments without inhibibiting its activity(Pogorelko et al, 2019).…”
Section: Introductionmentioning
confidence: 99%